Parallel execution of SVM training using graphics processing units (SVMTrGPUs) - Salleh N.S.M.; Baharim M.F. (Institute of Electrical and Electronics Engineers Inc., 2023)
Array processing; Benchmarking; Computer graphics; Control systems; Diagnosis; Parallel processing systems; Pattern recognition; Program processors; Search engines; Vectors; World Wide Web; Computational problem; CUDA; Graphics Processing Unit; Graphics processing units; Pattern classification techniques; Performance analysis; UCW dataset; Vector processors; Support vector machines